2012
DOI: 10.2139/ssrn.2034284
|View full text |Cite
|
Sign up to set email alerts
|

Does Broadband Speed Really Matter for Driving Economic Growth? Investigating OECD Countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Based on different specifications Koutroumpis (2009) found broadband penetration to have a significant impact on GDP growth ranging from 0.3 to 0.9 percent in 15 EU-countries. Rohman and Bohlin (2012) also found that a doubling of broadband speed contributed 0.3 percentage points to growth compared with growth in the base year. Williams et al (2012) is one of the few studies thus far that has investigated the impact of 3G penetration on economic growth.…”
Section: Related Literaturementioning
confidence: 90%
“…Based on different specifications Koutroumpis (2009) found broadband penetration to have a significant impact on GDP growth ranging from 0.3 to 0.9 percent in 15 EU-countries. Rohman and Bohlin (2012) also found that a doubling of broadband speed contributed 0.3 percentage points to growth compared with growth in the base year. Williams et al (2012) is one of the few studies thus far that has investigated the impact of 3G penetration on economic growth.…”
Section: Related Literaturementioning
confidence: 90%
“…We are still therefore at an early stage in terms of gathering evidence of faster broadband's incremental impacts -over and above the impacts of broadband in general. Rohman and Bohlin (2012) undertook one of the first attempts to measure the impact on broadband speed on economic growth, utilising a combination of OECD data for 33 countries over the period 2008-2010 and a proprietary speed testing dataset. Their regression analysis found that the coefficient of average achieved downstream broadband speed was not statistically significant, but that the coefficient of broadband speed squared was significant and positive -suggesting a non-linear relationship between broadband speeds and GDP per capita growth.…”
Section: High Levels Of Labour and Product Market Regulation Are Assomentioning
confidence: 99%
“…Other estimates of net or gross consumer surplus from broadband include work byGoolsbee and Klenow (2006) andRosston et al (2010).29 See also the four other non-peer reviewed studies cited inTable 1ofRohman and Bohlin (2012), claiming to find broadband investment multipliers of 1.45 to 3.6.…”
mentioning
confidence: 99%